Workshop On Reduction Of Demand For Illicit Drugs In South-East Asia. - PPD&U, Pusat Penyelidikan Dadah & Ubat-Ubatan (Pusat Penyelidikan Dadah Dan Ubat-Ubatan Universiti Sains Malaysia, 1978)

(untitled)
The member Governments of the COLOMBO PLAN BUREAU, recognizing the increasing level of demand for illicit drugs - especially narcotic drugs in the South-East Asian region, and the problems associated with the assessment treatment and rehabilitation of those persons dependent on drugs suggested that the Drug Advisory Programme of the COLOMBO PLAN BUREAU investigate the feasibility of organising a regional workshop in this field.